Pengaruh Pembelajaran Sejarah Kebudayaan Islam terhadap Sikap Toleransi Siswa di MAN 3 Solok - Ulfa Hidayati; Hidra Ariza (YASIN, 2026)
Although studies on character education and the formation of students’ social attitudes have been widely discussed in previous research, studies that specifically examine the effect of Sejarah Kebudayaan Islam learning on students’ tolerance attitudes within the madrasah environment remain relatively limited. This study aims to analyze the effect of Sejarah Kebudayaan Islam learning on the tolerance attitudes of tenth-grade students at MAN 3 Solok. This study employed a mixed-methods approach with a quantitative survey design enriched by qualitative data, involving 31 students as respondents selected through the total sampling technique. Data were collected using questionnaires, interviews, and documentation, and were then analyzed using simple linear regression for the quantitative data and descriptive analysis for the qualitative data. The results showed that Sejarah Kebudayaan Islam learning had a significant effect on students’ tolerance attitudes, with a significance value of 0.049 (p < 0.05). Descriptively, most students were in the high tolerance category at 54.84%, while 32.26% were in the moderate category and 12.90% were in the very high category. These findings affirm that Sejarah Kebudayaan Islam learning plays a role in shaping students’ tolerance attitudes within the madrasah environment and strengthens the understanding of the function of history learning as a means of internalizing the values of tolerance. The implications of this study indicate the importance of optimizing Sejarah Kebudayaan Islam learning as part of strengthening character education in madrasahs.